Diagnosis of cancer of the cervix by targeting VPAC receptors on exfoliated cervical cells - Nerli, Rajendra B.; Vinchurkar, Kumar; Kalloli, Mahesh; Rangrez, Shadab; Ghagane, Shridhar C.; Thakur, Madhukar L. (Brazilian Journal of Oncology, 2023)
Introduction: Cervical cancer is a major cause of cancer morbidity and mortality in women. Screening for cervical cancer reduces mortality through early detection and treatment. The success of the screening for cervical cancer has been largely attributed to the use of Pap smear (Papanicolaou). The objective of this study was to assess the feasibility of detecting cervical cancer by targeting genomic VPAC receptors and compare the results with those of Pap-test.Material and Methods: Women ≥40 years of age underwent routine screening for cervical cancer. The cellular material obtained from the cervix was gently smeared on a clean glass slide. The slides were then stained according to Papanicolaou’s technique. Similarly, another set of prepared smears were used for VPAC receptor detection. Histopathological examination of the cervical biopsy was done and the results of all three tests were compared.Results: A total of 114 women attending the Gynaecology outpatient department of our hospital were included in the study. Histopathological examination (HPR) of the cervical biopsy revealed that 25 patients had cervical cancer and the remaining 89 were negative for cervical cancer. The Pap smear gave positivity for malignant cells in 20 (80%) of cases reconfirmed on HPR. The false positive rate and false negative rates were 4.5% and 20%, respectively. The VPAC receptors were positive in 23 (92%) of the 25 cases with cancer of the cervix. The false positive and false negative rates were 2.2% and 8%, respectively.Conclusions: Diagnosis of cancer of the cervix can be reliably made by targeting the genomic VPAC receptors. The test is simple to perform, reliable, reproducible and with minimal false positivity having a higher diagnostic accuracy.
Keywords: Diagnosis; Cervix uteri; Cancer symptoms